Spray vaccination with a safe and bivalent H9N2 recombinant chimeric NDV vector vaccine elicits complete protection against NDV and H9N2 AIV challenge - Xiaoquan Wang; Jing Dai; Wenhao Yang; Yao Yao; Jin Zhang; Kaituo Liu; Xiaolong Lu; Ruyi Gao; Yu Chen; Jiao Hu; Min Gu; Shunlin Hu; et al. (Veterinary Research)
Abstract Newcastle disease virus (NDV) and H9N2 avian influenza virus (AIV) represent significant pathogenic risks to the poultry industry, leading to considerable economic losses. Vaccination is a widely used preventive measure against these pathogens, yet the lack of a live bivalent vaccine targeting NDV and H9N2 AIV imposes a heavy vaccination burden. Previously, we constructed a genotype-matched chimeric NDV vector, LX-OAI4S, in which the genotype I NDV backbone was replaced with the ectodomain of haemagglutinin-neuraminidase (HN) and modified using the attenuated F gene from the genotype VII vaccine strain A-VII. Based on the LX-OAI4S vector, we successfully generated three H9N2 recombinant viruses: LX-OAI4S-NPU-HA, LX-OAI4S-MU-HA, and LX-OAI4S-HNU-HA. These recombinants incorporated the H9N2 HA gene, flanked by untranslated regions (UTRs) from the NP, M, or HN gene of the NDV LX strain, inserted between the P and M genes of LX-OAI4S. The vaccine candidate LX-OAI4S-NPU-HA induced a more robust immune response in chickens against H9N2 AIV and NDV than the other two recombinants. This response effectively protects against virus shedding and lethal virus challenge. Furthermore, spray vaccination with LX-OAI4S-NPU-HA showed protective efficacy against H9N2 AIV and NDV. This study offers a promising strategy for comprehensive protection in regions threatened by H9N2 AIV and NDV.